Vitamin D receptor gene FokI polymorphisms and tuberculosis susceptibility: a meta-analysis - Cao, Yan (Arch Med Sci, 2016)
INTRODUCTION: The association between FokI polymorphism of vitamin D receptor (VDR) and tuberculosis (TB) susceptibility has been investigated previously; however, the results were inconsistent and conflicting. In the present study, a meta-analysis was performed to assess the relationship between VDR FokI gene polymorphism and the risk of TB. MATERIAL AND METHODS: Databases including PubMed and Embase were searched for genetic association studies of FokI polymorphism of vitamin D receptor (VDR) and TB. Data were extracted by two independent authors and the pooled odds ratio (OR) with 95% confidence interval (CI) was calculated to assess the strength of the association between VDR FokI gene polymorphism and TB risk. Meta-regression and subgroup analyses were performed to identify the source of heterogeneity. RESULTS: Thirty-four studies with a total of 5669 cases and 6525 controls were reviewed in the present meta-analysis. A statistically significant correlation was found between VDR FokI gene polymorphism and increased TB risk in two comparison models: the homozygote model (ff vs. FF: OR = 1.37, 95% CI: 1.17–1.60; P(heterogeneity) = 0.001) and the recessive model (ff vs. Ff + FF: OR = 1.32, 95% CI: 1.14–1.52; P(heterogeneity) = 0.006). Meta-regression found no source contributing to heterogeneity. However, sub-group analyses revealed that there was a statistically increased TB risk in the East and Southeast Asian population. CONCLUSIONS: Synthesis of the available studies suggests that homozygosity for the FokI polymorphism of the VDR gene might be associated with an increased TB risk, especially in the East and Southeast Asian population. Additional well-designed, larger-scale epidemiological studies among different ethnicities are needed.